Towards A Mother-Language Based Multi-Lingual Education in Jharkhand - Pattanayak, Binay (Journal of Productive Discourse, 2023)
Jharkhand is a highly multi-lingual Indian state, which is home to at least 33 indigenous communities, who speak around 20 mother languages. The new state used to experience the highest dropout of children at primary level in India. The author set up a research centre on children’s languages, M-TALL Akhra. The mother-language based centre focused on research and innovation in language and education. It conducted a state wide linguistic survey, which revealed that 96 percent children in the state spoke in indigenous languages, which are very different from the school’s Hindi language. Children failed to understand the language of textbooks, teachers and examination. Hence, they left school. M-TALL Akhra developed bilingual picture dictionaries in 9 indigenous languages for children in early grades. Then ‘Bhasha Puliya’ (language bridge) with content for pre-school education was developed. The piloting enabled around 80% children to acquire desired school readiness. It led to expansion of the programme to 7,200 pre-school education centres. Finally, it was upscaled across the board with improvised contents. Then M-TALL Akhra developed culture sensitive primary textbooks in 16 indigenous languages in five scripts. These textbooks, published in 7 languages since 2016, are used by indigenous children in around a thousand schools. A second linguistic survey was conducted recently by M-TALL Akhra for the state to design a foundational literacy numeracy (FLN) roadmap for children as desired under the National Education Policy, 2022.